PENGARUH KEADILAN PAJAK, TARIF PAJAK, TEKNOLOGI & INFORMASI PERPAJAKAN, DAN SELF ASSESSMENT SYSTEM TERHADAP PERILAKU TAX EVASION WAJIB PAJAK ORANG PRIBADI (Wajib Pajak Orang Pribadi yang Terdaftar di KPP Pratama Demak) - Yoga Pratama, 13.05.52.0156; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2017)
This study examines aims to know the effect of tax justice, tax rates, technology and tax information, self assessment system on tax evasion behavior. This research was conducted in KPP Pratama (tax office) Demak with individual taxpayer respondents.The population if this study is a personal taxpayer who has freework or business in KPP Pratama (tax office) Demak. Sample used in this research is convenience sampling. Data collection technique using questionnaires filled by the respondents. The total sample obtained in this study were 93 respondents. The data collected then in if with statistical tools that is IBM SPSS Statistik 16.0. The result of this study indicate that tax justice, tax rates, technology &information taxation, self assessment system simultaneously affect the behavior of tax evasion. Variable of tax justice and self assessment system partially no effect on tax behavior. While the taxe rate and technology & information taxation variable affect the tax evasion behavior.Keywords: Tax Justice, Tax Rates, Technology & Information Taxation, Self Assessment System, Tax Evasion Behavior